Successful English Learners’ Autonomy: A Look into The Perspective of Ecology - Dwitiya Ari Nugrahaeni; Afi Normawati; Noor Sahid Kusuma Hadi Manggolo (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2023)
Despite the significant allocation of time and resources to formal classroom English teaching in Indonesia, the outcomes have not been found to be commensurate or equivalent. Despite all the constraints, a minority of EFL learners in Indonesia have have demonstrated exceptional achievements in their learning journey, earning them the recognition of successful learners. This narrative research aims to study the participants’ out-of-class learning experience viewed from the perspective of ecology. To gain extensive exploration of the experience, this study incorporated the participants’ language learning careers (LLC). In order to complement the data and to gain deeper insights into the participants’ experiences, follow-up interviews were also conducted. The result demonstrated that the participants exercised their autonomous learning strategies in three dimensions of learning, namely the emergence of interest, the creation of learning opportunities, and the boundaries crossing. Through these dimensions, the participants navigate and manage the resources, opportunities, and constraint in their learning journey. This study provides insights into the management of learning beyond the classroom through the awareness of the environment.